PENGARUH PENDAPATAN MARGIN MURABAHAH DAN PENDAPATAN IJARAH TERHADAP LABA BERSIH PADA BANK MUAMALAT INDONESIA PERIODE 2018-2022 - Susantri, Saktia Hestu; Idwal, Idwal; Liza, Citra (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to determine whether there is a partial and simultaneous effect of Murabahah margin income and Ijarah income on net profit at Bank Muamalat Indonesia for the 2018-2022 period. To test this, researchers used descriptive quantitative methods with secondary data collection techniques in the form of Bank Muamalat Indonesia's annual financial statements for 2018-2022. The data analysis technique used is multiple regression using the SPSS program. From the results of research and discussion, it was found that Murabahah margin income and Ijarah income had no influence on net profit either partially or simultaneously.